The Director's Prism : E. T. A. Hoffmann and the Russian Theatrical Avant-Garde - Posner, Dassia N. (Book collections on Project MUSE., 2016)
The Director's Prism investigates how and why three of Russia's most innovative directors - Vsevolod Meyerhold, Alexander Tairov, and Sergei Eisenstein - used the fantastical tales of German Romantic writer E.T.A. Hoffmann to reinvent the rules of theatrical practice. Because the rise of the director and the Russian cult of Hoffmann closely coincided, Posner argues, many characteristics we associate with avant-garde theater - subjective perspective, breaking through the fourth wall, activating the spectator as a co-creator - become uniquely legible in the context of this engagement. Posner examines the artistic poetics of Meyerhold's grotesque, Tairov's mime-drama, and Eisenstein's theatrical attraction through production analyses, based on extensive archival research, that challenge the notion of theater as a mirror to life, instead viewing the director as a prism through whom life is refracted. A resource for scholars and practitioners alike, this groundbreaking study provides a fresh, provocative perspective on experimental theater, intercultural borrowings, and the nature of the creative process.